Relação entre os padrões oceanográficos e as rotas migratórias de tartarugas marinhas - Correa, Thayusky da Penha (2017)
Sea turtles perform long migrations in the ocean throughout their life cycle. Monitoring the cycle and its spatial and temporal complexity has been facilitated by the use of telemetry data and satellite imagery. Telemetry is a tool that has been providing tracking of sea turtle movements, and also allows the integration of oceanographic data in the analyzes, which increases the understanding of the ecology and the spatial distribution of these animals. Some studies have already used this methodology and demonstrated the patterns of displacement of sea turtles and areas of intense use in different oceanic regions. The present study analyzed the routes traveled by 31 individuals of sea turtle tracked on the coast of Brazil and into the South Atlantic Ocean between 2005 and 2009. The individuals belonged to 4 different species: Dermochelys coriacea (Leatherback turtle) Caretta caretta (Loggerhead turtle), Eretmochelys imbricata (Hawsbill turtle) and Lepidochelys olivacea (Olive Ridley). The thesis studies the relationship between migratory movements performed (post-nesting routes, travel to feeding and breeding areas) and the processes and oceanographic features that occurred in the tracking period. From the geographic location data provided by transmitters installed in the sea turtle hull, it was possible to calculate the travel speed of individuals and seek other informations about the marine surface environment such as the sea surface temperature (SST), the concentration of chlorophyll, current velocities (derived from sea surface height anomalies). After the analysis of telemetry and environmental data, it was concluded that the oceanic features are important factors in determining the recorded movement patterns, and that physical processes as the variability of SST influence the movement of the animals. In addition, the destinations of these animals tended to be to coastal regions with high concentrations of chlorophyll (therefore rich in phytoplankton). The speed average of the individuals during the routes was generally higher than the active current, showing that animals actively swim to their destination regardless of the speed and direction of currents. The species had similar displacement strategies, for example the routes of the species C. caretta, E. imbricata and L. olivacea had a more uniform, with persistent pattern on the continental shelf north and northeast of Brazil. However, the pattern of the D. coriacea species can not be said due to the low number of individuals analyzed even though both were significantly dispersed. The results obtained here are consistent with the previous literature, adding new knowledge about the behavior of sea turtle species occurring in the South Atlantic Ocean and its relationship with the environmental conditions during their offshore movements.